Analytical assessment of the current trends of capitalization of enterprises on the stock market - Mykola Lotoczkyy (Cхід, 2013)
The development of market of capitals in Ukraine takes place in the conditions of permanent change of the economic state of affairs, that affects instability of development of his constituents. Tendency of fund market of Ukraine, which were researched in the article, testify the existence of considerable potential for him further development. In the basis of such development are such factors: the personal interest of most subjects of menage in realization of additional capital issue; presence of considerable amount of potentially perspective subjects of menage, the shares of which are substantially underestimated.